1996
DOI: 10.1007/bf00051787
|View full text |Cite
|
Sign up to set email alerts
|

Impact of selection and breeding on the genetic diversity in Douglas-fir

Abstract: Genetic changes following domestication of Douglas-fir were studied using isozyme data derived from two generations of seed orchards and their 49 wild progenitor populations. In addition, the breeding, production, and infusion populations used in the seed orchards were compared to their wild counterparts. Several parameters of gene diversity were measured (number of alleles per locus N a, per cent of polymorphic loci PLP, and expected heterozygosity H, and population divergence D). These measures were similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 30 publications
(34 reference statements)
7
42
0
Order By: Relevance
“…The genetic and life history characteristics of forest trees result in populations, which are robust and resilient to genetic change. Consequently, many studies have found that artificial selection, breeding, and silviculture have had minor genetic effects on most tree species (Yazdani et al 198, Muona et al 1987, El-Kassaby and Ritland 1996, Savolainen 2000, Wellman et al 2003. Despite similar levels of genetic diversity reported in this study, differences in the distribution of alleles between maternal and progeny populations were observed (Table 4), mainly among rare alleles with frequencies ranging from 0.00 to 0.036.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic and life history characteristics of forest trees result in populations, which are robust and resilient to genetic change. Consequently, many studies have found that artificial selection, breeding, and silviculture have had minor genetic effects on most tree species (Yazdani et al 198, Muona et al 1987, El-Kassaby and Ritland 1996, Savolainen 2000, Wellman et al 2003. Despite similar levels of genetic diversity reported in this study, differences in the distribution of alleles between maternal and progeny populations were observed (Table 4), mainly among rare alleles with frequencies ranging from 0.00 to 0.036.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the linear deployment concept also assumes that the gametic contribution is representative of the orchard's parental linear representation. Finally, irrespective of which breeding strategy is implemented or seed orchard design is used, the main goal of the tree improvement endeavour is to reach an ideal balance between genetic gain and genetic diversity (Chaisurisri and El-Kassaby 1994;El-Kassaby and Ritland 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The above results indicate that phenotypic selection at the early stage of breeding of highly polymorphic species does not significantly reduce genetic variability, likely due to the sampling of trees for plantation establishment from widely distributed natural populations (El-Kassaby & Ritland 1996). These results are confirmed in more recent study for Picea glauca (Namroud et al 2012), where single-nucleotide polymorphisms (SNPs) were used to assess the potential impact of artificial selection for height growth on the genetic diversity.…”
Section: Seed Productionmentioning
confidence: 54%